Decade of the dacoits - Sahito, Imdad Hussain (Oxford University Press, 2005)
The word Dacoit translates roughly as "highwayman" and is a particularly feared phenomenon in some parts of Pakistan and India, most especially in the Pakistani Province of Sindh. The dacoits of Sindh are famous for their daring raids, and their capacity to loot, plunder, even murder and kidnap, and disappear swiftly into the jungle hideouts of their forest habitats. During the ten-year period from 1984-1994, the dacoits of Sindh became almost all-powerful, espcially in the towns and rural areas of the Province, and the police, even the army, could not contain them. This book traces the history of the dacoits of Sindh, and investigates the origins of the phenomena, and examines the forces that gave impetus to the problem, and even succored the dacoits in terrorizing the local population with impunity